A novel high-efficiency white hyperbranched polymer derived from polyfluorene with green and red iridium(III) complexes as the cores. (July 2016) - Sun, Jing; Wang, Hua; Xu, Huixia; Zhang, Tiaomei; Li, Lu; Li, Jie; Wu, Yuling; Xu, Bingshe; Zhang, Xinwen; Lai, Wenyong
Abstract: A new kind of single triple-color hyperbranched polymer PF-Ir(ppy)2 (pytzph)m-Ir(piq)2 (pytzph)n was designed and synthesized, in which green and red iridium(III) complexes acted as cores and blue polyfluorene acted as backbone. PF-Ir(ppy)2 (pytzph)m-Ir(piq)2 (pytzph)n (m = 5, n = 5 and m = 25, n = 5) had higher quantum efficiency than PF-Ir(piq)2 (pytzph)5. The energy transfer from green core bis(2-phenylpyridine)[3-(2-pyridyl)-5-phenyl-1, 2, 4-triazole]iridium(III) [Ir(ppy)2 (pytzph)] with high triplet energy level (ET = 2.58 eV) to red core bis(1-phenylisoquinolinato)[3-(2-pyridyl)-5-phenyl-1, 2, 4-triazole]iridium(III) [Ir(piq)2 (pytzph)] (ET = 2.12 eV) could realize by intermediate poly(9, 9-dioctylfluorene) (PF) segments. A typical single emitting-layer device with the configuration of ITO/PEDOT:PSS (40 nm)/PF-Ir(ppy)2 (pytzph)m-Ir(piq)2 (pytzph)n (80 nm)/TPBi (40 nm)/LiF (0.8 nm)/Al (100 nm) was fabricated. Among the white polymers, PF-Ir(ppy)2 (pytzph)5-Ir(piq)2 (pytzph)5 exhibited excellent electroluminescent properties with a Commission Internationale Ed I'eclairage (CIE) coordinate of (0.32, 0.34) and a maximum luminous efficiency of 11.49 cd/A. Highlights: Triple-color white-light polymers were designed and synthesized. Polyfluorene acts as the backbone in the hyperbranched polymers. Green Ir(ppy)2 (pytzph) and red Ir(piq)2 (pytzph) act as the cores in the hyperbranched polymers. The introduction of green Ir(ppy)2 (pytzph) has improved the electroluminescent performance.